KONSEP DASAR PENDIDIKAN ISLAM ANAK USIA DINI PERSFEKTIF HADITS - Ahd Gozali Gozali (JEA (Jurnal Edukasi AUD), 2021)
Children who are a mandate for their parents and teachers, they must consider a good education for them from an early age. Rasulullah has implemented several rules how should teach children. This research is a qualitative research with literature study and hermeneutic approach to the hadiths related to early childhood education. It was found that early childhood education in the perspective of the prophet's hadith should focus on the formation of noble character and worship to to Allah. Early childhood education must contain a curriculum that objects to the child's soul and body, including faith education, amaliyah, morality and skills education. In modern education termed cognitive, affective, and psychomotor.